Stability of maxillary anterior crowding treatment - Quaglio,Camila Leite (2012)
OBJECTIVE: To evaluate the stability and the relapse of maxillary anterior crowding treatment on cases with premolar extraction and evaluate the tendency of the teeth to return to their pretreatment position. METHODS: The experimental sample consisted of 70 patients of both sex with an initial Class I and Class II maloclusion and treated with first premolar extractions. The initial mean age was 13,08 years. Dental casts' measurements were obtained at three stages (pretreatment, posttreatment and posttreatment of 9 years on average) and the variables assessed were Little Irregularity Index, maxillary arch length and intercanine. Pearson correlation coefficient was used to know if some studied variable would have influence on the crowding in the three stages (LII1, LII2, LII3) and in each linear displacement of the Little irregularity index (A, B, C, D, E) in the initial and post-retention phases. RESULTS: The maxillary crowding relapse ( LII3-2) is influenced by the initial ( LII1), and the teeth tend to return to their pretreatment position. CONCLUSION: The results underline the attention that the orthodontist should be given to the maxillary anterior relapse, primarily on those teeth that are crowded before the treatment.